The effect of spotwelds and structural adhesives on static and dynamic characteristics of vehicle body design. (October 2021) - Tuncer, Gozde; Mansouri, Deniz; Şendur, Polat
Spotwelding and structural adhesive applications are two important processes in the automotive industry as they are closely associated with the functional requirements, weight, and cost of the vehicle. Even though there is a vast body of literature on their mathematical models, the effect of these processes on key vehicle performance indices and optimization is rather limited. Besides, the weight benefit of these processes in terms of functional requirements has not been investigated. There are multiple objectives of the paper to fill this gap: (i) to quantify the effect of structural adhesives on the key performance indices (KPIs) of a vehicle body, (ii) to rank the components based on their gauge sensitivities for body KPIs using topometry optimization, (iii) to assess the weight impact of the structural adhesive applications using the gauge sensitivity results, (iv) to determine the optimum layout of the structural adhesive applications using topology optimization, (v) to present a methodology for automotive original equipment manufacturers (OEMs) to determine the "critical welds" on the vehicle body and reduce the number of spotwelds as a potential cost reduction action. For this purpose, a validated finite element model of 2010 Toyota Yaris has been used. Optimization of the structural adhesives and spotwelds was carried-out using SIMP (Solid Isotropic Material with Penalization) based topology optimization. The thickness of each panel is ranked using topometry optimization results. Automotive OEMs can use the proposed methodology to optimize the structural adhesives or spotwelding processes in their product development cycle.